1985
DOI: 10.1212/wnl.35.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Head injury as a risk factor for Alzheimer's disease

Abstract: A case-control study was performed in which the frequency of prior head injury was assessed in 78 patients with dementia of the Alzheimer type (DAT) and 124 control subjects matched for age, sex, and race. A history of head injury with loss of consciousness was reported in 25.6% of patients and 5.3% and 14.6% of hospital and neighborhood controls, respectively. Matched-pair analysis of patients and hospital controls yielded an odds ratio of 4.50, which was significant (p less than 0.01). The ranges of times of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
111
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(118 citation statements)
references
References 0 publications
4
111
0
3
Order By: Relevance
“…We discuss the factors that influence the strength and direction of the relationship between TBI and Alzheimer's disease, and the implications of this body of research for patient care and future research. is associated with increased risk for degenerative neurocognitive conditions resulting in dementia [11][12][13][14][15]. AD is by far the most commonly diagnosed subtype of dementia, accounting for up to 80% of all dementia cases [16].…”
Section: Future Perspective: Implications For Patient Carementioning
confidence: 99%
“…We discuss the factors that influence the strength and direction of the relationship between TBI and Alzheimer's disease, and the implications of this body of research for patient care and future research. is associated with increased risk for degenerative neurocognitive conditions resulting in dementia [11][12][13][14][15]. AD is by far the most commonly diagnosed subtype of dementia, accounting for up to 80% of all dementia cases [16].…”
Section: Future Perspective: Implications For Patient Carementioning
confidence: 99%
“…Risk factors for development of dementia in population studies of elderly normal subjects may be of prognostic value in patients with mild cognitive impairment. The risk factors that derive from the literature include age, 29,30 a family history of dementia, 31 history of head injury, 32,33 depression, 34,35 as well as low pre-morbid intelligence and education. [36][37][38] Female gender has been noted to be a risk factor for dementia in a number of studies, 30,[39][40][41] although this has not been found in others.…”
Section: Clinical Risk Factors For Development Of Dementia and Admentioning
confidence: 99%
“…The interest in the role of Ab after TBI has grown from epidemiological studies that have demonstrated an association between a history of TBI and the development of AD later in life (Graves et al, 1990;Mortimer et al, 1985Mortimer et al, , 1991Salib and Hillier, 1997;Szczygielski et al, 2005;Van Den Heuvel et al, 2007). Additionally, post-mortem studies have demonstrated AD-like deposits of Ab in as many as 30% of TBI victims (Roberts et al, 1991(Roberts et al, , 1994.…”
Section: Introductionmentioning
confidence: 99%